THE INFLUENCING FACTORS IN CLEANER PRODUCTION ADOPTION ON THE ALUMINIUM PROCESSING INDUSTRY - Devi Agustina; Agus Dwi Wicaksono; Christia Meidiana (JEMIS (Journal of Engineering & Management in Industrial System), 2023)
Cleaner Production (CP) practices comprised environmental strategy perpetually applied in the production, processes, and services to bolster efficiency, safety, and environmental friendliness. Some factors are to be considered to achieve a cleaner production strategy: stakeholders establishment, surveys, utilization, and impact, as well as how the top management devote their practices towards cleaner production. Combining with the mindset of sustainable stocks and resources, this exercise of cleaner production provides advantages of minimum toxic wastes and residues. In this study, we prioritize this practice to be applied in the aluminum industry, of which cleaner production action has not yet been employed. Small and medium businesses now no longer have enough monetary assets to put money into cleaner production practices because they require high-cost investment. This study aimed to determine the factors that have an impact on the application of cleaner production. The method used is regression analysis. The regression analysis results showed that three variables were tested to be significant and had a Root Mean Square Error (RMSE) value of 3.05 which means good. Three variables that affected the implementation of cleaner production include measurement of fuel usage, efforts to improve production process efficiency, and waste reuse by product. From the calculation results, the coefficient of determination (R2) was 0.550 (the influence was quite strong). The results of this study can be used as a recommendation for the government to increase the implementation cleaner production in Jombang Regency.